Sorption isotherms and thermodynamic properties of the dry silage of red tilapia viscera (Oreochromis spp.) obtained in a direct solar dryer (2021)
ABSTRACT: The sorption isotherms, thermodynamic properties and calculation for confirming the isokinetic theory of dry chemical silage of red tilapia viscera (Oreochromis spp.) obtained in a direct passive solar dryer were determined. Sorption isotherms were carried out at 15, 25, 35 and 45 C using a static gravimetric method. The curves obtained were adjusted to eight equations. The isosteric heat of sorption (net and total) and the thermodynamic parameters were determined based on the Clausius-Clapeyron equation and the enthalpy–entropy compensation theory was applied to adsorption isotherms. The sorption isotherms obtained were of type III of Brunauer classification. The Peleg model best described the experimental data. In all cases, the isosteric heat decreased while the moisture content increased. The value of isokinetic temperature (TB) was found to be less than harmonic mean temperature (Thm), the sorption of water in dry chemical silage is therefore controlled by entropic mechanisms and proceeds spontaneously.